Polymorphisms of heat shock protein 70 genes (HSPA1A, HSPA1B and HSPA1L) and susceptibility of noise-induced hearing loss in a Chinese population: A case-control study. - Yanhong Li; Shanfa Yu; Guizhen Gu; Guoshun Chen; Yuxin Zheng; Jie Jiao; Wenhui Zhou; Hui Wu; Zengrui Zhang; Huanling Zhang; Lihua He; Qiuyue Yang; et al. (PLoS ONE)
Noise-induced hearing loss (NIHL) is the second-most frequent form of sensorineural hearing loss. When exposed to the same noise, some workers develop NIHL while others do not, suggesting that NIHL may be associated with genetic factors. To explore the relationship between single nucleotide polymorphisms (SNPs) in heat shock protein 70 (HSP70) genes (HSPA1A, HSPA1B and HSPA1L) and susceptibility to NIHL in Han Chinese workers exposed to noise, a case-control association study was carried out with 286 hearing loss cases and 286 matched with gender, age, type of work, and exposure time, drawn from a population of 3790 noise-exposed workers. Four SNPs were selected and genotyped. Subsequently, the effects of the alleles and genotypes of the three HSP70 genes (HSPA1A, HSPA1B and HSPA1L) on NIHL were analyzed by using a conditional logistic regression. A generalized multiple dimensionality reduction (GMDR) was applied to further detect an interaction between the four SNPs. Compared with the combined genotypes CC/TC, carriers of the TT genotype of rs2763979 appeared to show greater susceptibility to NIHL (P = 0.042, adjusted OR = 1.731, 95% CI 1.021-2.935). A significant interaction between rs2763979 and CNE was found (P = 0.029), and a significant association was found between TT of s2763979 and NIHL (P = 0.024, adjusted OR = 5.694, 95%CI 1.256-25.817) in the 96 dB (A)≤CNE<101 dB (A) group. The results suggest that the rs2763979 locus of the HSP70 genes may be associated with susceptibility to NIHL in Chinese individuals, and other HSP70 genes may also be susceptibility genes for NIHL, but the results must be further replicated in additional independent sample sets.